Numerical Simulation Study on the Dynamic Processes and Evolution Laws of Multiple Granular Flows in a Gully - LEI Ming; ZHANG Liang; YE Chen; WANG Xiekang (工程科学与技术)
Objective Under the impact of dynamic loads like earthquakes and rainstorms, the instability and sliding of the front slope can significantly diminish the anti-sliding capacity of the subsequent slope. This, in turn, may trigger a chain of secondary landslides, ultimately resulting in multiple granular flows. Due to the high unpredictability and destructive power of granular flow, research on their dynamic characteristics, disaster mechanisms, and comprehensive prevention and control technologies has long been a core topic and frontier direction in the field of geological hazards. To address this, we carry out simulation research on the dynamic processes and evolution laws of multiple granular flows under different terrain conditions.Methods Firstly, it is necessary to choose a suitable numerical calculation model. At present, numerical simulation methods for the movement of loose slope can be mainly divided into two theoretical systems: continuous medium models and discontinuous medium models. Although continuous medium models have significant advantages in theoretical maturity, computational efficiency, and engineering applicability, they have inherent limitations in simulation accuracy. On the one hand, it is difficult to capture micro mechanical behaviors such as contact force chain evolution and collision energy dissipation at the granule scale. On the other hand, the simulation accuracy for the movement of the front slope is insufficient. These key mechanical behaviors are precisely the core of revealing the mechanism of geological disasters. Compared to continuous medium models, discontinuous media models can accurately obtain the overall kinematic characteristics of loose slopes at the macroscopic scale, and can also analyze the time-varying laws of progressive failure of internal rock masses at the microscopic scale. Due to its unique advantages in simulating the movement of granules, the Discrete Element Method has emerged as the most representative numerical computation approach in discontinuous medium models. Consequently, it is employed herein to perform numerical experiments on the movement and deposition of multiple granular flows under varying terrain conditions. Secondly, we perform numerical simulations of two laboratory physical model experiments on granular flow with different granule sizes reported in the literature. Comparison between numerical results and experimental data from the literature validates the effectiveness and accuracy of the Discrete Element Method in simulating granular flow. Finally, based on the Discrete Element Method, numerical simulations can be conducted to investigate the movement and deposition of multiple granular flows under different channel slopes and friction coefficients. The research focuses on analyzing how these factors influence on flow velocity, entrainment effect, downstream sediment supply and deposition morphology, in order to reveal the dynamic processes and evolution laws of multiple granular flows.Results and Discussions During the first granular flow, both granule velocity and kinetic energy increase with the secondary slope angle but decrease with the friction coefficient. Notably, the flow duration increases significantly with decreasing secondary slope angle and friction coefficient. Granule average potential energy increases with decreasing secondary slope angle yet exhibits low sensitivity to friction coefficient variation. Cross-sectional sediment transport mass follows a unimodal distribution-initially rising then declining-with peak magnitude decaying systematically along the flow path. In subsequent granular flows, the entrainment effect leads to a substantial decrease in both granule kinetic energy and velocity. Compared with the first granular flow, subsequent ones feature shorter durations and higher energy dissipation rates. The velocity and displacement of base granules increase significantly as the friction coefficient decreases and the secondary slope increases. The mass of the granular flow shows a step-by-step decreasing pattern along the flow direction, and the granule mass passing through the same cross-section is notably lower than that in the first granular flow. Regarding accumulation morphology, the initial granular flow event exhibits a profile transition from fan-shaped to elliptical with increasing secondary slope angle and decreasing friction coefficient. The loose bed materials formed in the early stage are laterally pushed by subsequent granules, and their blocking effect further increases the accumulation width compared with the first granular flow. Furthermore, as the secondary slope increases or the friction coefficient decreases, the lateral extension range of the deposit expands with the longitudinal extension distance, which corresponds to a reduction in deposit thickness. This study constructs a generalized three-level slope channel model to mitigate uncertainties from complex boundaries, though it does not account for channel deflection or underlying surface conditions.It should be noted that channelized granular flows exhibit complex grain-size distributions spanning from millimeter-scale sand to meter-scale boulders.. However, as the number of granules increases, the computational load of numerical simulation rises significantly, leading to a substantial increase in computer running time. Therefore, this study specifically focuses on simulating the transport and deposition processes of granules with sizes ranging from 30 cm to 150 cm. This article uses the Discrete Element Method to explore the dynamic processes and evolution laws of multiple granular flows in a channel, but the numerical experiments only involve two sediment supply events. The granule size distribution, granule shape, and incoming sediment mass remain unchanged during each supply, and the influence of granule fragmentation on the movement and deposition of granular flows is not considered. Due to the significant slope variations in natural channels, the physical model in this study consists of three slope segments. However, when investigating the impact of slope gradient on the transport and deposition characteristics of multiple granular flows, only the secondary slope is modified. While these simplifications focus on core granular flow mechanisms, they warrant gradual improvement in future research.Conclusions The results reveal that terrain conditions-incorporating factors like channel slope gradients and surface roughness-shape distinct bed structures by modifying the energy dissipation mechanisms of granules, such as frictional collisions, intergranular friction, and kinetic energy conversion, while also influencing their movement patterns (including velocity variations, flow direction changes, and entrainment behaviors) and deposition characteristics (such as accumulation thickness and lateral spread scope). These formed bed structures, in turn, exert a significant control over the evolutionary trends of multiple granular flows. By clarifying the connection between terrain conditions and multiple granular flows behaviors, this research can support the formulation of scientific prevention and control strategies-such as hazard zoning and engineering measure design-targeting multiple granular flows in mountainous channels.